The impact of indoor rowing exercise on leptin and adiponectin levels in young adult obese - a pilot study/ Nur Farhana Md Yunus ... [et al.] - Md Yunus, Nur Farhana; Durairajanayagam, Damayanthi; Omar, Mazlifah; Jathin, Romizan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Among the obese, high leptin levels is said to be a sign of leptin resistance, while low adiponectin levels are due to the reciprocal relationship between these adipokines in relation to adipocytes. Leptin and adiponectin are hormones that are linked to the development of obesity-related diseases. Thus, an optimal exercise programs needs to be identified as an intervention to reduce leptin and increase adiponectin levels among obese individuals. The effects of exercise on these adipokines in obese subjects are inconclusive. Rowing is a non-weight bearing form of exercise and can be regarded as one of the safest exercises for obese adults. However, the effect of indoor rowing exercise on leptin and adiponectin among obese individuals is not well reported. This study determined the impact of a 12-week indoor rowing exercise on leptin and adiponectin; and the correlation between pre- and post-exercise changes in these adipokines in young adult obese subjects. Twelve young adult obese males and females (aged 18-35 years, BMI ≥30kg/m2) were divided into an Intervention and a Control Group (n=6 respectively). The Intervention Group performed rowing exercise 3 times per week for 12 weeks. Subjects in the Control group continued with their daily activities as per their normal routine. All variables were measured before and after 12 weeks in each group as well as between the groups. Levels of the two adipokines were quantified using ELISA. There was no significant difference in both adipokines following indoor rowing exercise. However, there was a significant negative correlation between pre- and post-exercise changes in leptin and adiponectin. In conclusion, indoor rowing exercise as performed in this study did not seem to significantly affect these adipokines in young adult obese subjects. This could be due to the small sample size, gender mix and exercise regimen among these subjects.